If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 4) = 2(x + 4) Reorder the terms: 3(4 + 2x) = 2(x + 4) (4 * 3 + 2x * 3) = 2(x + 4) (12 + 6x) = 2(x + 4) Reorder the terms: 12 + 6x = 2(4 + x) 12 + 6x = (4 * 2 + x * 2) 12 + 6x = (8 + 2x) Solving 12 + 6x = 8 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 12 + 6x + -2x = 8 + 2x + -2x Combine like terms: 6x + -2x = 4x 12 + 4x = 8 + 2x + -2x Combine like terms: 2x + -2x = 0 12 + 4x = 8 + 0 12 + 4x = 8 Add '-12' to each side of the equation. 12 + -12 + 4x = 8 + -12 Combine like terms: 12 + -12 = 0 0 + 4x = 8 + -12 4x = 8 + -12 Combine like terms: 8 + -12 = -4 4x = -4 Divide each side by '4'. x = -1 Simplifying x = -1
| 3(2)-2y= | | 3(1)-2y=7 | | 3(0)-2y=7 | | (6x+1)+(5x+8)= | | 3(-1)+2y=7 | | 3(-2)+2y=7 | | 3(1)+2y=10 | | 2(6x+4)=3x+10 | | f(-6)=2x+8 | | 10-6a=-4a+-12 | | 3(-1)+2y=10 | | 4y-6=7y-48 | | 3(-2)+2y= | | 4(3x-1)7-x=-2x+3+9x | | 2(2x+4)=5x+4 | | (8x-3y)+(-8x+3y)=16-16 | | 3z+30=51 | | (10m-30)=28 | | X-10=3(X-10) | | y=-0.08x+4.48 | | 5(3r-5)=9r+17 | | 3(2x-5)(2x-5)-(3x-7)(5-2x)=0 | | 2(3x+4)=2x+3 | | 2x+4y=156 | | 4x+-56=12 | | 3(2)-5y=10 | | 24=k(5) | | 3(13-4x)=7-16x | | 3(2)-5=10 | | 3(1)-5y=10 | | 3(0)-5y=10 | | 10x-345=12 |